Ethical Frontiers of the State - Milne, A. J. M. author. aut Link
X, 338 p.
Keywords: The moral justification for government is, that it is needed to promote the community's interest. What is that interest an interest in? Upon what basis can disagreements about the community's interest and individual interests be reconciled? Can democracy enable dissatisfaction with their reconciliation to be lived with? Perhaps, if people are prepared to meet the requirements of democratic citizenship. What are these requirements, and what is their justification? These are the questions with which this book is concerned.